Assessing the Credibility and Motivation in E-Learning during the Covid-19 Education Shift - Brika, Said Khalfa; Abderzag, Fouzi Tahar; Musa, Adam Ahmed; Mehaouat, Labidi Hocine; Mukhtar, Mohannad Abbas; Alabsy, Nabil Mohamed (Journal of Ecohumanism, 2024)
The purpose of this study is to assess the complex relationship between e-learning credibility and student motivation during COVID-19. Online education is growing, so educators, institutions, and governments must understand student motivation and e-learning attitudes. The study examines student COVID-19 management to discover crucial components. We explain the difficulty of e-learning credibility and its large impact on student motivation to help educators and scholars. Four research hypotheses guided the investigation; a descriptive survey design and an online questionnaire were utilized to collect data from 480 Saudi higher education students. Because of these factors, this study examines e-learning methods, tools, and approaches in today’s complicated landscape. How e-learning systems motivate and engage students depends on interaction, adaptability, and reliability. This case study combines rapid educational technology advancement with pandemic-level disruption. It examines how e-learning will change post-pandemic education. The study’s findings are noteworthy given the COVID-19 pandemic’s widespread use of e-learning. Politicians and schools utilize them to engage pupils and enhance e-learning amid emergencies. This study may provide teachers, administrators, and instructional designers with confidence in e-learning. It may improve online learning. E-learning credibility and motivation should be studied across institutions and student populations.